Association of Levels of Anxiety in Resident Doctors with Factors related to the Postgraduate Training in Teaching Hospitals - Sehrish Zehra; Syed Muhammad Zulfiqar Hyder Naqvi; Muhammad Zafar Iqbal Hydrie; Samira Faiz; Farhan Muhammad Qureshi; Syed Imtiaz Ahmed Jafry (Journal of Bahria University Medical and Dental College)
Objective: To assess level of anxiety, its associated factors and coping strategies in postgraduate trainees of public and private teaching hospitals of Karachi Study Design and Setting: It was a cross-sectional study. The data was collected from different major teaching hospitals February 2019 till April Methodology: A total of 230 postgraduate trainees were interviewed using a pre-tested structured questionnaire specifically designed for this study which included General Anxiety Disorder-7 Scale and Brief COPE Questionnaire. Data were analyzed on SPSS version 21. Chi-square test and multinomial logistic regression was performed and P-value <0.05 was considered as statistically significant Results: Total 39.6% of the participants had no anxiety, 34.3% had mild, 16.1% had moderate while 10.0% had severe anxiety. Being single, nuclear family system and low monthly household income had higher odds of having severe anxiety (Adjusted Odds Ratio (AOR); 5.50, 95% CI 1.38,22.14, AOR; 2.50, 95% CI 0.83,7.51 and AOR; 3.17, 95% CI 0.96,10.49 respectively). Severe anxiety was also highly associated with irregular sleep pattern (AOR; 2.06, 95% CI 0.70, 6.06), no daily exercise (AOR; 5.01, 95% CI 1.21, 2.69) and lack of job satisfaction (AOR; 2.64, 95% CI 0.90, 7.90). The most frequently adapted coping strategies by participants who were found to have anxiety were, planning (89.9%), acceptance (87%) and religion (85.6%). Conclusion: Postgraduate trainees should be provided with psychological counseling and support at workplace to keep them mentally healthy to enhance their everyday performance in dealing and treating patients.